Disease Severity, Activity, Impact, and Control and How to Assess Them in Patients with Hereditary Angioedema - Bygum, Anette; Busse, Paula; Caballero, Teresa; Maurer, Marcus (Frontiers in Medicine, 2017)
Hereditary angioedema (HAE) is a group of rare, potentially life-threatening, and frequently debilitating diseases characterized by recurrent, and often with an unpredictable onset, of swelling attacks. HAE is heterogeneous, with considerable differences between its subtypes, patients and even within the same patient over time. During the past few years several new on demand and prophylactic therapies have become available for HAE, allowing for individualized treatment. Therefore, to optimize HAE management, it is important to determine in all patients, the severity of their attacks, their disease activity, its therapeutic control and its impact on their quality of life (QoL). In this manuscript, we review the existing tools to assess these aspects of HAE management, many of which are patient reported outcome (PRO) instruments. We conclude by outlining the current gaps in the assessment of HAE disease severity and its therapeutic control, outlining which tools are need to be developed to allow for a comprehensive assessment of all patients, and specially, children with HAE.